2013
DOI: 10.3945/ajcn.112.044453
|View full text |Cite
|
Sign up to set email alerts
|

Estimating dietary costs of low-income women in California: a comparison of 2 approaches

Abstract: Background: Currently, no simplified approach to estimating food costs exists for a large, nationally representative sample. Objective: The objective was to compare 2 approaches for estimating individual daily diet costs in a population of low-income women in California. Design: Cost estimates based on time-intensive method 1 (three 24-h recalls and associated food prices on receipts) were compared with estimates made by using less intensive method 2 [a food-frequency questionnaire (FFQ) and store prices]. Low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“… 78 Another study also found relatively weak agreement between diet costs estimated with standard prices and with prices actually paid by individuals. 93 …”
Section: Resultsmentioning
confidence: 99%
“… 78 Another study also found relatively weak agreement between diet costs estimated with standard prices and with prices actually paid by individuals. 93 …”
Section: Resultsmentioning
confidence: 99%
“…Aaron et al 13 similarly found a relatively small mean difference of $0.14 between the two methods that they compared, with 95% limits of agreement of over $7.00. This compared with a mean diet cost of around $6.00 using either method.…”
Section: Discussionmentioning
confidence: 93%
“…12 In contrast, our study compares two different diet cost methods. The study by Aaron et al 13 also compared different diet cost methods, but used a frequency questionnaire to assess dietary intake, whereas this study was based on cost estimates from 4-day diet diaries. As such, this study should assist researchers in interpreting estimates of diet cost provided by such databases when applied to diet diaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FFQs typically lack specific detail regarding serving sizes, such that this information is often based on standardised portion sizes of specific foods published in National dietary guidelines (Vlismas et al, 2010), which does not account for individual variation (Rangan et al, 2009). Other studies use self-reported 24 h recall (Aaron et al, 2013) or dietary histories in a face-to-face interview (Turrell and Kavanagh, 2005), which are prone to recall bias and poor reliability at the individual level (Thomas B, 2002). Few studies use 7-day diet records (Rao et al, 2013), commonly referred to as the 'gold standard' dietary assessment tool (Hoidrup et al, 2002).…”
Section: Dietary Assessmentmentioning
confidence: 99%